2012
DOI: 10.3201/eid1803.111278
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infection in HIV-infected Persons

Abstract: To determine whether hepatitis E virus (HEV) is a cause of hepatitis among HIV-infected persons, we evaluated 1985–2009 data for US military beneficiaries. Evidence of acute or prior HEV infection was detected for 7 (4%) and 5 (3%) of 194 HIV-infected persons, respectively. HEV might be a cause of acute hepatitis among HIV-infected persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 15 publications
4
36
3
1
Order By: Relevance
“…A serologic study of samples from U.S. military personnel and their families found that HEV seropositivity in HIV-positive persons was associated with a lower CD4 ϩ cell count and higher HIV viral load, independent of antiretroviral drug use (303). A cohort of Swiss HIV patients were more likely to have chronic HEV infections if their CD4 ϩ cell counts were low (273), but a study in France, which also detected a chronic HEV case with low CD4 ϩ levels, suggested that overall anti-HEV IgG seropositivity was unrelated to CD4 ϩ cell count (272).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…A serologic study of samples from U.S. military personnel and their families found that HEV seropositivity in HIV-positive persons was associated with a lower CD4 ϩ cell count and higher HIV viral load, independent of antiretroviral drug use (303). A cohort of Swiss HIV patients were more likely to have chronic HEV infections if their CD4 ϩ cell counts were low (273), but a study in France, which also detected a chronic HEV case with low CD4 ϩ levels, suggested that overall anti-HEV IgG seropositivity was unrelated to CD4 ϩ cell count (272).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…More recent studies focusing on detection of anti-HEV IgM, IgG, or RNA have identified both acute (266,(303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313) and chronic (266,(268)(269)(270)(271)(272)(273)(274) HEV infections in HIV-positive patients, though it remains unclear whether or not seroprevalence is any greater in people with HIV (272,273,300,309,310,(314)(315)(316)(317)(318). Chronic HEV infections in HIV-positive individuals have been associated with quick progression to cirrhosis (269)(270)(271), though it is not clear whether HEV-linked cryptogenic cirrhosis is more common in HIV-infected individuals than in the general population (310,311,315,319).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…Regarding HEV, it is an emerging cause of autochthonous hepatitis in Europe (14) and a new causative agent of acute and chronic hepatitis in HIV-infected persons (15)(16)(17)(18)(19). Nonetheless, HEV seroprevalence has not been found to date to differ statistically significantly between HIV-seropositive and -seronegative patients reference to GenBank sequence accession no.…”
mentioning
confidence: 99%
“…However, HEV co-infection in patients with HIV is not common and, to date, less than 20 cases have been documented in the literature, and only a handful have had chronic infection, the majority of these cases become cleared of HEV spontaneously. 4,[62][63][64][65][66][67][68][69][70][71][72] In contrast to recipients of a SOT, the key risk factor that determines the development of chronic infection in HIV patients is a low CD4 count. In the five chronic cases described so far, all had CD4 counts <250 mm 3 .…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%
“…[62][63][64][65][66][73][74][75][76][77] One study retrospectively tested for HEV in 194 HIV-positive US military beneficiaries and showed that HEV was the cause of abnormal liver function tests in only 4% of HIV-infected individuals. 65 Serum transaminitis caused by HEV was no more common in this population than in the general population.…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%